Relationship of iodine excess with thyroid function in 6-year-old children living in an iodine-replete area - Lee, Yun Jeong; Cho, Sun Wook; Lim, Youn-Hee; Kim, Bung-Nyun; Kim, Johanna Inhyang; Hong, Yun-Chul; Park, Young Joo; Shin, Choong Ho; Lee, Young Ah (Frontiers in Endocrinology, 2023)
Background: Adequate iodine intake is essential for growing children, as both deficient and excessive iodine status can result in thyroid dysfunction. We investigated the iodine status and its association with thyroid function in 6-year-old children from South Korea. Methods: A total of 439 children aged 6 (231 boys and 208 girls) were investigated from the Environment and Development of Children cohort study. The thyroid function test included free thyroxine (FT4), total triiodothyronine (T3), and thyroid-stimulating hormone (TSH). Urine iodine status was evaluated using urine iodine concentration (UIC) in morning spot urine and categorized into iodine deficient (< 100 μg/L), adequate (100–199 μg/L), more than adequate (200–299 μg/L), mild excessive (300–999 μg/L), and severe excessive (≥ 1000 μg/L) groups. The estimated 24-hour urinary iodine excretion (24h-UIE) was also calculated. Results: The median TSH level was 2.3 μIU/mL, with subclinical hypothyroidism detected in 4.3% of patients without sex differences. The median UIC was 606.2 μg/L, with higher levels in boys (684 μg/L vs. 545 μg/L, p = 0.021) than girls. Iodine status was categorized as deficient (n = 19, 4.3%), adequate (n = 42, 9.6%), more than adequate (n = 54, 12.3%), mild excessive (n = 170, 38.7%), or severe excessive (n = 154, 35.1%). After adjusting for age, sex, birth weight, gestational age, body mass index z-score, and family history, both the mild and severe excess groups showed lower FT4 (β = − 0.04, p = 0.032 for mild excess; β = − 0.04, p = 0.042 for severe excess) and T3 levels (β = − 8.12, p = 0.009 for mild excess; β = − 9.08, p = 0.004 for severe excess) compared to the adequate group. Log-transformed estimated 24h-UIE showed a positive association with log-transformed TSH levels (β = 0.04, p = 0.046). Conclusion: Excess iodine was prevalent (73.8%) in 6-year-old Korean children. Excess iodine was associated with a decrease in FT4 or T3 levels and an increase in TSH levels. The longitudinal effects of iodine excess on later thyroid function and health outcomes require further investigation.